John Marney, Beyond the Mulberries; an Anthology of Palace-style Poetry by Emperor Chien-wen of the Liang Dynasty (503-551), Taipeh, Chinese Materials Center, 1982, VIII + 240 pp. - Maeth Ch., Russell (El Colegio de México, 1986)
-